Analisis Tindak Tutur Asertif Dalam Proses Interaksi Belajar Mengajar Antar Guru Dan Peserta Didik Pada Mata Pelajaran Bahasa Indonesia: Assertive Speech Acts in Indonesian Language Learning Interactions between Teachers and Students - Wahyu Saputra (Sumule Indonesia Publishing, 2026)
Classroom interaction in Indonesian language learning is not only a medium for delivering material but also a pragmatic space where teachers and students negotiate meaning through their utterances. This study aims to describe the forms, types, and pragmatic meanings of assertive speech acts used by teachers and students in Indonesian-language learning interactions at SMP Negeri 111, West Jakarta. The study employed a descriptive qualitative method because the primary data consisted of natural oral utterances produced during classroom interaction. Data were collected through classroom observation, audio recording, attentive listening, and note-taking; they were then transcribed, coded, classified, and interpreted based on the theory of assertive speech acts and the context of the speech event. The findings show 52 assertive speech acts consisting of stating (19 data), informing (18 data), suggesting (3 data), boasting (2 data), complaining (5 data), demanding (4 data), and reporting (1 datum). The dominance of stating and informing indicates that Indonesian language learning interactions are primarily constructed through utterances that present propositions, clarify learning material, and build shared understanding between teachers and students. The novelty of this study lies in its contextual reading of assertive speech acts in junior high school Indonesian language learning, particularly by linking the frequency of these acts to their pragmatic functions in classroom participation. These findings imply that teachers need to manage assertive utterances not only as information-delivery tools, but also as strategies for encouraging students to express ideas, report learning results, and respond critically to classroom discourse